Understanding the role of miRNAs in cervical cancer pathogenesis and therapeutic responses - Chauhan, Prashant; Pramodh, Sreepoorna; Hussain, Arif; Elsori, Deena; Lakhanpal, Sorabh; Kumar, Rahul; Alsaweed, Mohammed; Iqbal, Danish; Pandey, Pratibha; Al Othaim, Ayoub; Khan, Fahad (Frontiers in Cell and Developmental Biology, 2024)
Cervical cancer (CC) is the most common cancer in women and poses a serious threat to health.Despite familiarity with the factors affecting its etiology, initiation, progression, treatment strategies, and even resistance to therapy, it is considered a significant problem for women.However, several factors have greatly affected the previous aspects of CC progression and treatment in recent decades. miRNAs are short non-coding RNA sequences that regulate gene expression by inhibiting translation of the target mRNA. miRNAs play a crucial role in CC pathogenesis by promoting cancer stem cell (CSC) proliferation, postponing apoptosis, continuing the cell cycle, and promoting invasion, angiogenesis, and metastasis. Similarly, miRNAs influence important CC-related molecular pathways, such as the PI3K/AKT/mTOR signaling pathway, Wnt/β-catenin system, JAK/STAT signaling pathway, and MAPK signaling pathway. Moreover, miRNAs affect the response of CC patients to chemotherapy and radiotherapy. Consequently, this review aims to provide an acquainted summary of onco miRNAs and tumor suppressor (TS) miRNAs and their potential role in CC pathogenesis and therapy responses by focusing on the molecular pathways that drive them.